VARIATION OF CONCENTRATION OF DEXTRAN WITH GLYCINE AT 308 K AND AT FREQUENCY 5MHZ - Subhraraj Panda (International Journal of Modern Agriculture, 2020)
The density (ρ) viscosity (η) and ultrasonic speed (U), at 308 K have been measured in the systems of different concentration of dextran with glycine in aqueous medium. The ultrasonic seed have been measured by using ultrasonic interferometer at frequency of 5MHz in different concentration of dextran with glycine in aqueous medium. The acoustic parameters such as “free volume, internal pressure, absorption coefficient, Rao’s constant and Wada’s constant” are calculated using the measured parameters ρ, η and U. The variation of acoustic parameters with different concentration of dextran with glycine leads to the analysis of molecular motion and various types of inter-molecular interaction and their strength of the constituent between solute (dextran) and solvent (glycine 2(M))